Nonrotation of gut with nutcracker syndrome: a rare presentation - Jha, Saket; Deshmukh, Shahaji; Kulkarni, Apoorva; Gupta, Abhaya; Kothari, Paras (International Surgery Journal, 2021)
Nutcracker syndrome is a rare diagnosis which presents with hematuria, abdominal pain and is caused by left renal vein entrapment in between abdominal aorta and superior mesenteric artery. Symptomatic presentation of rotational abnormalities of gut are rare in adults though it can present with abdominal pain. Simultaneous presence of nonrotation with nutcracker syndrome was very rarely reported in literature. The authors reported a 38 year old female who presented with chronic pain in left side of abdomen and was diagnosed as nutcracker syndrome with nonrotation of gut. Patient underwent Ladd’s procedure with left renal vein transposition. Patient was asymptomatic on follow up. Search of literature showed only two previous cases being reported making it a very rare presentation.